Lysophosphatidic acid promotes endometrial decidualization in recurrent implantation failure patients by regulating LPAR6 - Wang, Shanshan; Zhang, Yang; Zhang, Xindong; Cai, Xinyu; Hong, Min (Frontiers in Cell and Developmental Biology, 2025)
BackgroundImpaired decidualization is associated with recurrent implantation failure (RIF) and lysophosphatidic acid (LPA) is known to play an important role in decidua formation. However, the specific impact of LPA in endometrial decidualization during RIF remains unclear.MethodsMetabolomics analysis was performed to identify differentially expressed metabolites (DEMs) in RIF patients Expression of the LPA receptor subtypes, LPAR1-6, was detected in both GEO datasets and clinical endometrial samples. An in vitro decidualization model was established by treating human endometrial stromal cells (hESCs) with medroxyprogesterone acetate (MPA) and 8Br-cAMP. The functional roles of LPA and its receptors (LPAR1-6) during decidualization were further investigated via RT-qPCR, ELISA, immunofluorescence, CCK-8 proliferation assays, Western blotting, and immunohistochemistry.ResultsLPA was identified as a pivotal metabolite in RIF. Among the LPA receptors, LPAR1 and LPAR6 were highly expressed during in vitro decidualization of hESCs. LPA treatment significantly increased the levels of insulin-like growth factor binding protein-1 (IGFBP1) and prolactin (PRL) and promoted cytoskeletal reorganization Inhibition of LPAR6-but not LPAR1-attenuated hESCs decidualization, as evidenced by reduced mRNA and protein levels of decidual markers and altered cellular morphology. CCK-8 assays revealed that neither LPA stimulation nor LPAR1-6 inhibition significantly affected hESC proliferation. Furthermore, LPAR6 blockade abolished the enhancing effects of LPA on IGFBP1 and PRL mRNA expression, as well as PRL protein secretion. These results suggest that LPAR6 plays a critical role in LPA-mediated regulation of decidualization.ConclusionLPA plays a significant role in the decidualization process of hESCs by regulating LPAR6, rather than LPAR1, providing insights into potential therapeutic target for RIF.